Does hypnosis result in greater weight loss compared to conventional approach?. Issue 2 (3rd October 2022) - Roslim, Nurul Afiedia; Ahmad, Aryati; Mansor, Mardiana; Aung, Myat Moe Thwe; Hamzah, Farrahdilla; Shahril, Mohd Razif; Lua, Pei Lin
ABSTRACT: Hypnosis has been increasingly used in recent years as an alternative treatment to maintain well-being. Yet, limited evidence is available regarding its role in weight management, especially in Malaysia. Hence, this quasi-experimental study was conducted to evaluate the effectiveness of hypnosis on weight loss and body composition (body mass index, waist circumference and body fat percentage) among staff and students of a public university in Terengganu, Malaysia. Participants with body mass index (BMI) ≥ 25.0 kg/m 2 were randomly assigned to either intervention group (IG = 53) or control group (CG = 54), for 12 weeks. All participants received health education (diet + exercise + behavioral recommendations) with those in IG had additional three hypnotherapy sessions, once a month. Body weight was measured at week 1, 7, and 12 while body compositions were measured at weeks 1 and 12. Descriptive, univariate, and repeated-measures analysis of covariance (ANCOVA) were utilized. A total of 104 participants completed the trial (mean age = 26.28 ± 8.01; female = 82.2%; BMI = 31.39 ± 4.89). A significant weight loss was observed in the intervention (−4.61%) and control (−3.04%) groups (mean difference = −1.57; 95%CI: −2.59, −0.54; p = .003) after 12 weeks. Participants that frequently practiced self-hypnosis lost more weight (−6.27%; t(50) = −5.331, p < .001). Body fat percentage and waist circumference did not significantly change from baseline in both groups. Essentially, the positive outcomes indicated the promising potential of hypnosis as an alternative tool in facilitating weight loss efforts for those in need.